Diagnosing, monitoring and managing behavioural variant frontotemporal dementia. Issue 7 (2nd October 2017) - Piguet, Olivier; Kumfor, Fiona; Hodges, John
Summary:   Behavioural variant frontotemporal dementia is characterised by insidious changes in personality and interpersonal conduct that reflect progressive disintegration of the neural circuits involved in social cognition, emotion regulation, motivation and decision making. The underlying pathology is heterogeneous and classified according to the presence of intraneuronal inclusions of tau, TDP‐43 or, occasionally, fused in sarcoma proteins. Biomarkers to detect these histopathological changes in life are increasingly important with the development of disease‐modifying drugs. A number of gene abnormalities have been identified, the most common being an expansion in the C9orf72 gene, which together account for most familial cases. The 2011 international consensus criteria propose three levels of diagnostic certainty: possible, probable and definite. Detailed history taking from family members to elicit behavioural features underpins the diagnostic process, with support from neuropsychological testing designed to detect impairment in decision making, emotion processing and social cognition. Brain imaging is important for increasing the level of diagnosis certainty over time. Carer education and support remain of paramount importance.